1982
DOI: 10.1111/j.1365-2184.1982.tb01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of a low molecular weight inhibitor of epidermal DNA synthesis

Abstract: Abstract. An attempt has been made to purify factors present in aqueous extracts of pig epidermis which inhibit epidermal cell proliferation. A lipophilic factor of low molecular weight (less than 10,000), has been shown to inhibit DNA synthesis as measured by the uptake of tritiated thymidine in mouse ear epidermis. Purification by alcohol precipitation, ethyl acetate extraction and silicic acid column chromatography produced a fifteen‐fold increase in the specific activity of the inhibitory action. It seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…One of the main problems in assaying for chalone activity in skin extracts is that inhibitory activity tends to be found spread over a wide range of fractions, and it has recently been suggested that a low molecular weight substance may bind to several types of larger species, and thus appear in several fractions from gel filtration or ion-exchange chromatography (Quirk et al 1982). These workers proposed that the active substance was a lipid, and began with an ethanolic extraction of epidermal scrapings from slaughtered pig skin.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main problems in assaying for chalone activity in skin extracts is that inhibitory activity tends to be found spread over a wide range of fractions, and it has recently been suggested that a low molecular weight substance may bind to several types of larger species, and thus appear in several fractions from gel filtration or ion-exchange chromatography (Quirk et al 1982). These workers proposed that the active substance was a lipid, and began with an ethanolic extraction of epidermal scrapings from slaughtered pig skin.…”
Section: Introductionmentioning
confidence: 99%